2018
DOI: 10.1111/asj.13112
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversities and population structures of four popular Myanmar local cattle breeds

Abstract: Local cattle breeds are popular in Myanmar because they make excellent draught animals, so it is of fundamental importance that their genetic diversities and population structures are elucidated for breeding and conservation purposes. In this study, we characterized the genetic diversities and population structures of four popular Myanmar local cattle breeds and five native cattle populations from neighboring countries (Bangladesh, Laos, Cambodia, and Vietnam) using the GGP Bovine 50K array. The mean observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…In the experiments of Gowda et al [ 4 ] and Hattakum et al [ 5 ], Holstein dairy cows and steer were used as experimental animals, which are different in the breed of cattle used in our experiment and Maneerat et al [ 9 ]. In contrast, Myanmar local cattle and fattening Thai steers, both are Zebu type ( Bos indicus ) [ 18 , 19 ], were used, respectively. Jardstedt et al [ 20 ] reported that feed intake was influenced by the breed of cattle, whereas Charolais cattle have a higher feed intake than Hereford cattle.…”
Section: Resultsmentioning
confidence: 99%
“…In the experiments of Gowda et al [ 4 ] and Hattakum et al [ 5 ], Holstein dairy cows and steer were used as experimental animals, which are different in the breed of cattle used in our experiment and Maneerat et al [ 9 ]. In contrast, Myanmar local cattle and fattening Thai steers, both are Zebu type ( Bos indicus ) [ 18 , 19 ], were used, respectively. Jardstedt et al [ 20 ] reported that feed intake was influenced by the breed of cattle, whereas Charolais cattle have a higher feed intake than Hereford cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, genotypes of 344 VDC were merged with genotypes of 277 reference animals using the command "--merge," resulting in a data set of 623 animals with genotypes of 14,786 overlapping SNPs. Then, a quality control process was applied, which removed 4079 SNPs with either call rate ≤95% or minor allele frequency (MAF) ≤5% using command "--geno 0.05" and "--maf 0.05" (Cheruiyot et al, 2018;Lwin et al, 2018). An individual with a sample call rate of <90% was also removed, using the command "--mind 0.1" (Cheruiyot et al, 2018;Lwin et al, 2018).…”
Section: Merged Genotype Data and Quality Controlmentioning
confidence: 99%
“…Then, a quality control process was applied, which removed 4079 SNPs with either call rate ≤95% or minor allele frequency (MAF) ≤5% using command "--geno 0.05" and "--maf 0.05" (Cheruiyot et al, 2018;Lwin et al, 2018). An individual with a sample call rate of <90% was also removed, using the command "--mind 0.1" (Cheruiyot et al, 2018;Lwin et al, 2018).…”
Section: Merged Genotype Data and Quality Controlmentioning
confidence: 99%
See 2 more Smart Citations